2023
DOI: 10.3390/chemistry5010023
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Impact of Tungsten on the Catalytic Properties of Ammonia-SCR V2O5-WO3/TiO2 Catalysts: Geometric vs. Electronic Effects

Abstract: The SCR performance of V2O5-WO3/TiO2 SCR-catalysts characterized by different surface W density (2.1W/nm2 and 9.5W/nm2) and different surface V density varying in the range 1–8V/nm2 has been investigated in order to clarify existing controversies on the preferential involvement of electronic and geometric effects in the catalytic properties. It was found that tungsten has a weak effect on the VOx cluster size distribution through contraction of dilution effect. In contrast, the optimal interaction between W an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There is long argument about the nature of the active sites, Marberger et al 34 observed that the Lewis acid site is the primary site for the SCR reaction, while Brønsted acid sites served as a storage of NH 3 , and this theory is also supported by others. [72][73][74][75] To represent the reactivity of SCR catalysts more accurately, the adsorption of NH 3 is modeled with a similar approach as H 2 O. The adsorption configuration is determined by surface scans of adsorption energy over the Lewis acid sites, for each configuration with different level water coverage.…”
Section: 4mentioning
confidence: 99%
“…There is long argument about the nature of the active sites, Marberger et al 34 observed that the Lewis acid site is the primary site for the SCR reaction, while Brønsted acid sites served as a storage of NH 3 , and this theory is also supported by others. [72][73][74][75] To represent the reactivity of SCR catalysts more accurately, the adsorption of NH 3 is modeled with a similar approach as H 2 O. The adsorption configuration is determined by surface scans of adsorption energy over the Lewis acid sites, for each configuration with different level water coverage.…”
Section: 4mentioning
confidence: 99%